Role of Clinical Microbiology Laboratory for Prevention of Infection in Hospital Settings: Bangladesh Perspective - Shahid, Sazzad Bin (Bangladesh Journal of Medical Microbiology, 2023)
Abstract not available Bangladesh Journal of Medical Microbiology, July 2022;16(2):36-37